SYMPTOM PROFILE OF SUBSTANCE INDUCED PSYCHOSIS VERSUS PSYCHOSIS WITH COMORBID SUBSTANCE AT KUWAIT ADDICTION TREATMENT CENTER (World Bulletin of Public Health, 2022)
The determination of possible indicators of the abnormalities could facilitate their detection and management because the differential diagnosis of substance-induced psychotic disorder and psychosis with comorbid substance is especially difficult while in a severe admittance when psychotic symptoms are at their worst. The article compares individuals with substance-induced psychosis and individuals with psychosis and concomitant drug to examine the phenomenological elements and many factors affecting the clinical picture
Keywords: Substance use disorder; Dual diagnosis; Psychosis with comorbid substance use; psychosis